Identificação de linfonodos sentinela da mama com azul de metileno em modelo canino - Rolim, Ranieri dos Santos (2010)
Objectives. To develop an experimental model for identification of sentinel lymph node (SLN) of breast bitch with the use of methylene blue and compares it with the patent blue, both associated with technetium. Methods. 23 dogs, there was the marking of the SLN of the first upper pair of breasts to inject 0.2 ml of Tc-99m phytate bound to (99m) and 0.5 ml of patent blue Guerbet V 2,5 % in subpapilar spaces right breast and 0.2 ml of 99mTc and 0.5 ml of 1% methylene blue in the same spaces left breast. Results. In the right breast biopsy techniques using 99mTc SLN and blue dye are in agreement. Of the 23 SLN studied, only one was not flushed nor uptake. The patent blue was effective in 100% when compared with the two methods together. The left breast of 23 SLN studied, only two non-stained and one was not uptake, this difference was not statistically significant. The SLN biopsy technique using methylene blue appeared with a 91.3% effectiveness when used alone and 100% when associated with 99mTc. Conclusion: The use of methylene blue associated with the radiotracer technique can be considered as potential research intraoperative SLN of breast, suggesting a less costly and less allergenic effects that blue patent.